Clinical Presentation and Risk Factors for Molar-Incisor and Second Primary Molar Hypomineralization: A Cross-Sectional Study - Thamirys da Costa Rosa; Fernanda Mafei Felix da Silva; Fernanda Gabriela de Fátima Vieira; Alexandre Rezende Vieira; Andrea Fonseca Gonçalves; Marcelo de Castro Costa; Aline de Almeida Neves (Association of Support to Oral Health Research (APESB), 2024)
Objective: To identify the clinical presentation of molar incisor hypomineralization (MIH) and hypomineralization of second primary molars (HSPM), including the distribution patterns of presence and severity of lesions, and to investigate the association of risk factors during the pre-and postnatal period with the presence of lesions. Material and Methods: This cross-sectional study was conducted with 160 individuals (72 with MIH/HSPM and 88 without lesions). The symmetry analysis regarding the presence and severity of MIH/HSPM was evaluated in pairs of homologous and opposite teeth. Sociodemographic and medical information was obtained using a detailed questionnaire. Data were analyzed by means of chi-square tests, Student's t-test, and logistic regression (p<0.05). Results: Symmetry of presence and severity of hypomineralization lesions were present in homologous permanent teeth in 53.8% and 70.5% of cases, respectively, with statistically significant results only for the symmetrical pattern of severity of MIH lesions in the maxillary first molars (p=0.016) and mandibular first molars (p=0.02). Otherwise, a non-symmetric presence was statistically significant in homologous second primary molars (p=0.002) and opposite primary and permanent teeth (p≤0.001). An association between MIH/HSPM and systemic diseases during pregnancy and children medication was found (p<0.05); however, no evidence was found between these and MIH/HSPM severity. Conclusion: The symmetric pattern of severity of MIH lesions was statistically significant in permanent homologous teeth. Risk factors during pre and postnatal periods may be related to MIH/HSPM; however, these do not seem to interact with severity.